Insight into the photodegradation mechanism of bisphenol-A by oxygen doped mesoporous carbon nitride under visible light irradiation and DFT calculations - Bukola Shittu, Fatimah; Iqbal, Anwar; Ahmad, Mohammad Norazmi; Yusop, Muhammad Rahimi; Mohamad Ibrahim, Mohamad Nasir; Sabar, Sumiyyah; D. Wilson, Lee; Yuli Yanto, Dede Heri (Royal Society of Chemistry (RSC), 2022)
Oxygen doped mesoporous carbon nitride (O-MCN) was successfully synthesized through one-step thermal polymerization of urea and glucose utilizing nanodisc silica (NDS) from rice husk ash as a hard template. The CO2 gas, NH 3 and water vapor produced during the thermal process reshaped the morphology and textural properties of the of O-MCN compared to pristine mesoporous carbon nitride (MCN). Highest bisphenol A (BPA) removal achieved under visible light irradiation was 97%, with 60% mineralization ([BPA] ¼ 10 mg L1 : catalyst dosage ¼ 40 mg L-1 ; pH ¼ 10; 180 min). In addition to mesoporosity, the sub-gap impurity states created from the oxygen doping reduced recombination rate of photogenerated carriers. Holes (h+ ) and superoxide (O2c) were identified as the predominant active species responsible for the photodegradation process. The photodegradation route was proposed based on the intermediates detected by LC-time-of-flight/mass spectrometry (LC/TOF-MS). The Density of States (DOS) showed that oxygen doping resulted in a higher photoactivity due to the stronger localization and delocalization of the highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO). The adsorption pathway of the BPA on the O-MCN and MCN was successfully predicted using the DFT calculations, namely molecular electrostatic potential (MEP), global and local descriptors.